Effect of Different Acids Addition on Chiral Separation of Phthalylvaline by Quinine Carbamate Based Chiral Stationary - Fegas, Rachid; Zerkout, Said; Taberkokt, Meriem; Bettache, Zhor; Righezza, Michel (Asian Journal of Chemistry, 2013)
The quinine carbamate type chiral stationary phase used for direct enantiomer separation of amino acid was studied. The influence of mobile phase composition, methanol and different acids were systematically investigated to gain an insight into the overall chiral recognition mechanism.